CRIMINAL OFFENSE OF ATTACKING THE HONOR OF THE PRESIDENT AND VICE PRESIDENT OVER CONCERNS ABOUT CRIMINALIZING FREEDOM OF OPINION IN THE PUBLIC - Zidane Zykrie Balfas; Erwin Asmadi (Inspiring Law Journal, 2026)
This research is motivated by the reform of the national criminal law through Law Number 1 of 2023 concerning the Criminal Code which again regulates the offense of assaulting the honor of the President and Vice President and causing polemics in the community regarding the potential criminalization of freedom of opinion. In the context of a democratic country, the existence of these norms raises a tension between the protection of the dignity and dignity of state officials and the guarantee of human rights, especially freedom of expression. Therefore, this study aims to analyze the regulation of the offense of assaulting the honor of the President and Vice President in the old Criminal Code and the 2023 Criminal Code, examine its limitations and qualifications, and assess its urgency from the perspective of protecting public freedom of opinion.The method used in this study uses a type of normative juridical research with a descriptive nature and a legislative, conceptual, and case approach. The data sources used include primary, secondary, and tertiary legal materials obtained through literature studies both offline and online. The data collection technique is carried out through library research, while the data analysis uses a qualitative method by examining relevant legal norms, principles, and doctrines to obtain systematic and comprehensive conclusions.Based on this research, it can be described that the regulation of the offense of assaulting the honor of the President and Vice President in the 2023 Criminal Code shows a fundamental difference compared to the old Criminal Code, especially through the change in the nature of the offense to a complaint offense that provides more proportional protection. Furthermore, the limitations and qualifications of the offence have been formulated by emphasizing the element of